Research of non‐destructive testing for aluminium sheaths of HV cables using ultrasonic‐guided waves. Issue 16 (13th February 2019) - Junping, Cao; Hang, Jiang; Shaohua, Wang; Yong, Yang; Luyao, Zhou; Peng, Jiang
Abstract : The method of fast non‐destructive testing for aluminium sheaths of high‐voltage (HV) cables using ultrasonic‐guided waves is proposed. The dispersion curve is calculated by solving the dispersion equation from the simplified model of aluminium sheaths of HV cables; thus, the appropriate wave mode and excitation frequency can be chosen. Three defects including crack, perforation, and sag have been set up. Then, the simulation experiments have been carried out for aluminium sheaths of HV cables based on the theoretical analysis and finite element simulation. The results show that cracks with the loss ratio of the sectional area over 4.25% can be detected by the T (0, 1) mode whose frequency is 32 kHz; the amplitude of the flaw echo increases along with the loss ratio of the crack. Theoretical analysis, finite element simulation, and experiments prove the feasibility of aluminium sheaths using ultrasonic‐guided waves, providing a new method for the defect testing.